A GIS methodology for planning sustainable renewable energy deployment in Portugal - Costa, P. (2020)
ABSTRACT: A Geographical Information System (GIS) methodology was developed to identify and characterize suitable areas for deploying renewable energy projects. The methodology enables to compute the sustainable renewable energy potential in an area under study and can be implemented for different spatial scales, ranging from local to national levels, while operating with different restriction layers. This GIS-based method has been successfully applied to wind energy deployment studies in Continental Portugal and other foreign countries (e.g. Venezuela, Mozambique among others). Results from several development plans using this methodology enable to conclude it is an adequate tool for planning sustainable renewable energy deployment both for onshore and offshore regions.